Pengaruh Brand Ambassador Dan Social Media Marketing Serta Online Customer Review Terhadap Keputusan Pembelian Produk Di Shopee - M Alwan Rosyidi; Asnawati (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study aims to analyze the effect of Brand Ambassadors, Social Media Marketing, and Online Customer Reviews on product purchasing decisions at Shopee, especially among users in Samarinda City. The method used is a quantitative approach with descriptive and explanatory design, involving 108 respondents selected through purposive sampling technique. Data was collected using a questionnaire with a 5-point Likert scale. The results of the analysis show that Brand Ambassador has no significant influence on purchasing decisions, with a t-count value of 0.818 and a significance of 0.415. In contrast, Social Media Marketing and Online Customer Review are proven to have a significant influence on purchasing decisions, with t-count values of 4.713 (significance 0.000) and 4.734 (significance 0.000), respectively. The coefficient of determination (Adjusted R²) shows that 54% of the variation in purchasing decisions can be explained by these three variables. These findings emphasize the importance of marketing strategies through social media and customer reviews in influencing purchasing decisions on e-commerce platforms.